Self-esteem levels in school-going adolescents across the slums of Karachi, Pakistan: a cross-sectional analysis - Naeem, Hira; Sharif, Sana; Sharif, Hina; Seemi, Tooba (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction For individuals to live their lives and integrate into society, self-esteem is an essential feeling. Self-esteem development depends on the environment in which children are nurtured. Assessment techniques using questionnaires include Rosenberg's self-esteem scale. Objective The study aimed to assess the self-esteem of school-going adolescents in slum areas. Methodology This school-based cross-sectional study was conducted in three understudied slum areas of Karachi, Pakistan. A standardized scale, the Rosenberg Self-esteem Scale (RSES), and a pre-tested demographic scale was used to assess the impact of gender, weight, academic performance, tuition, and parent's education level along with parent's strictness on the self-esteem of the understudied population of adolescents aged between 11 and 19 years included in the study. Parent consent was obtained before visiting the schools. Findings As per the collected data on self-esteem, among 539 school-going adolescents, 232 (43%) were male and 307 (57%) were female. Most students, 324 (60%), were in the 14–16 age range. Parents' education status and strictness towards their children, academic performance, and adolescent body mass index (BMI) influenced self-esteem levels. Conclusion The study found that age, parent's education, parent's strictness, BMI, and academic performance were linked to the levels of self-esteem in the target population regardless of gender. Children's surroundings play an imperative role in developing lower or higher self-esteem in children. Assessing adolescent's self-esteem can be a useful way to build strong self-confident youngster and also beneficial to treatment for those with psychosomatic complaints in their growing age.